The Influence of Online Customer Review, Viral Marketing, and Shopping Convenience on Purchase Decisions on Shopee: Gender as a Moderating Variable - Yunike (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Sabda Setia, 2026)
While e-commerce platforms like Shopee have integrated advanced digital marketing components, empirical gaps remain regarding how demographic profiles like gender moderate the effectiveness of these strategies within behavioral frameworks. Guided by the Theory of Planned Behavior (TPB), this study examines the partial, simultaneous, and moderated effects of online customer reviews, shopping convenience, and viral marketing on consumer purchase decisions on Shopee. Adopting a quantitative approach, survey data were gathered from 103 active Shopee users in Indonesia selected via purposive sampling and analyzed using Moderated Regression Analysis (MRA) in SPSS. The simultaneous and partial empirical findings reveal that online customer reviews and shopping convenience significantly and positively drive consumer purchase decisions. Conversely, viral marketing shows no significant partial effect. Furthermore, the interaction analysis clarifies that gender acts as a significant moderating variable, successfully moderating the relationship between these digital marketing factors and consumer buying decisions. This study enhances academic understanding by contextualizing TPB in digital retail and provides actionable insights for e-commerce marketers to optimize customized platform trust and navigation efficiency rather than over-relying on generic marketing campaigns.